2019
DOI: 10.1037/scp0000193
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patient feedback on Islamic spiritual healing in Brunei.

Abstract: Islamic spiritual healing is a complementary technique in traditional medicine that is very popular in Muslim-majority countries, in terms of its affordability, availability, and accessibility. However, lack of studies investigating feedback of the treatment despite its popularity and practices worldwide has left a void in the evidence of Islamic spiritual care aspect of conventional health care system. A retrospective study was conducted to determine the prevalence and patient feedback of spiritual healing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…There are only a few studies on the process and outcome of SIPs with international samples. Abdul Rahman et al (2019) analyzed feedback from 1,378 clients who had received treatments in an Islamic healing center in Brunei and found that 26%–32% of clients, especially those who had a spiritual disturbance, provided positive feedback about Islamic spiritual treatment. Using a randomized clinical trial of female cancer patients in Iran, Sajadi et al (2018) found that spiritual interventions led to significantly more improvements in spiritual well-being than nonspiritual interventions.…”
Section: Spiritually Integrated Psychotherapiesmentioning
confidence: 99%
“…There are only a few studies on the process and outcome of SIPs with international samples. Abdul Rahman et al (2019) analyzed feedback from 1,378 clients who had received treatments in an Islamic healing center in Brunei and found that 26%–32% of clients, especially those who had a spiritual disturbance, provided positive feedback about Islamic spiritual treatment. Using a randomized clinical trial of female cancer patients in Iran, Sajadi et al (2018) found that spiritual interventions led to significantly more improvements in spiritual well-being than nonspiritual interventions.…”
Section: Spiritually Integrated Psychotherapiesmentioning
confidence: 99%
“…This view lends support to Emmons’s (2000) conception of spiritual intelligence, implying that spirituality allows individuals to encounter problems, attain goals, manage their lives and discover meaning and significance. As noted by Abdul-Rahman (2017), many Muslim scholars touched upon the spiritual aspect of well-being. This notion is in light of the following Quranic verse: “And whoever turns away from My remembrance – indeed, he will have a depressed life, and We will gather him on the Day of Resurrection blind” (Quran, 20:124).…”
Section: Introductionmentioning
confidence: 99%
“…The following verse induces people to contemplate: “We will soon show them our signs in the Universe and in their own souls, until it will become quite clear to them that it is the truth” (Quran, Fusselat, 41:53). As suggested by Abdul-Rahman (2017), such contemplations foster people’s spirituality by abstracting positive feelings and meanings (e.g. perseverance, optimism, gratitude and inspiration).…”
Section: Introductionmentioning
confidence: 99%